Preparation of Feature Heading and Class Index Heading Using Computer - Gupta, B. S. S. (Journal of Information and Knowledge, 1970)
A schedule look-up procedure for the translation of Colon Class Number into the standard terms of the schedules to form a Feature Heading using a computer, is described. The methods used for recognising a devised isolate number and an unsought link are mentioned. The procedure for preparing cyclically permuted Class Index Headings is described briefly.